Cloud computing application model for online recommendation through fuzzy logic system - Shojaei, Elham (2018)
Cloud computing can offer us different distance services over the internet. We propose an online application model for health care systems that works by use of cloud computing. It can provide a higher quality of services remotely and along with that, it decreases the cost of chronic patient. This model is composed of two sub-model that each one uses a different service, one of these is software as a service (SaaS) which is user related and another one is Platform as a service (PaaS) that is engineer related. Doctors classify the chronic diseases into different stages according to their symptoms. As the clinical data has a non-numeric value, we use the fuzzy logic system in Paas model to design this online application model. Based on this classification, patienst can receive the proper recommendation through smart devices (SaaS model).